Insight into One Health Approach: Endoparasite Infections in Captive Wildlife in Bangladesh - Tilak Chandra Nath; Keeseon S. Eom; Seongjun Choe; Shahadat Hm; Saiful Islam; Barakaeli Abdieli Ndosi; Yeseul Kang; Mohammed Mebarek Bia; Sunmin Kim; Chatanun Eamudomkarn; Hyeong-Kyu Jeon; Hansol Park; et al. (Pathogens, 2021)
Introduction: Endoparasites in captive wildlife might pose a threat to public health; however, very few studies have been conducted on this issue, and much remains to be learned, especially in limited-resource settings. This study aimed to investigate endoparasites of captive wildlife in Bangladesh. Perception and understanding of veterinarians regarding one health and zoonoses were also assessed. Materials and Methods: A cross-sectional study was conducted from October 2019 to August 2020. A total of 45 fecal samples from 18 different species of wild animals (i.e., 11 species of mammals: herbivores, carnivores, and omnivores, six birds, and a single reptile species) were collected randomly. Parasitological assessments were done by modified formalin ether sedimentation technique and rechecked by Sheather’s sugar floatation technique. Molecular identification of Spirometra spp. was conducted by amplifying the cytochrome c oxidase 1 (cox1) gene. Questionnaire surveys among 15 veterinarians and an in-depth interview (IDI) with a zoo officer were conducted. Results: Helminths (Spirometra sp., Capillaria sp., Ascaridia/Heterakis, opisthorchiid, strongyles, acuariid, hookworms, roundworms, and unidentified nematode larvae) and protozoa (coccidian oocyst) were identified, and the overall prevalence was 48.9% (22/45). The cox1 sequences (341 bp) of the Bangladesh-origin Spirometra species from lion showed 99.3–99.7% similarity to the reference sequences of Spirometra decipiens (GenBank No: KJ599679.1; MT122766). The majority of study participants (86.6%) agreed about the importance of endoparasite control in zoo animals, and 73.3% expressed that the one health concept should be promoted in Bangladesh. Only 6.7% of veterinarians perceived confidence in diagnosing parasitic diseases and preventing antiparasiticidal resistance. Conclusions: In the present survey, we found a considerable prevalence of endoparasites in captive wildlife. For the first time, zoonotically important S. decipiens from lion was molecularly characterized in Bangladesh. Veterinarian training is required to improve parasite control knowledge and practice. This study highlights the need for routine parasitological assessment, promotion of one health, and improvement of the implementation of current parasite control strategies in zoo animals.